The development of successful industrial hypermedia applications - Fakun, D. (Cranfield University, 2000)
The changing manufacturing environment is putting pressure on shop floor operators. To help them cope with the pressures and support them in their tasks an industrial hypermedia application, a computerised information system (IS), has been proposed. However, resistance to IS by target users is a widespread problem. Therefore, companies need guidance on how to augment user acceptance, hence success, of these applications. A literature review on industrial hypermedia applications revealed that five research issues needed to be investigated. Among those issues were the lack of recommendations to hypermedia application developers and managers of manufacturing companies intending to invest in industrial hypermedia applications. This research makes a major contribution by providing a set of recommendations that when adopted may produce successful applications benefiting both the operators and the manufacturing company. This research started by reviewing management of information systems (MIS), human computer interaction (HCI) and hypermedia disciplines to deduce a set of hypothesised factors or constructs that might influence success, measured through intention to use and subjective use. The factors, individual, organisational, task and system, were employed to develop two predictive and explanatory theoretical models, a pre-implementation and a post-implementation model. Empirical data for the constructs in the models were collected in the work place and statistically analysed. Based on the analysis, the ecologically valid findings suggest that shop floor operators can use industrial hypermedia applications and are rational when deciding whether or not to use the applications. The factor having a significant positive influence on user acceptance was an attribute of the application, namely perceived usefulness. The latter is influenced by other factors that can be controlled by developers and facilitated or mitigated by managers. With the proposed recommendations developers and managers may make informed decisions and meet the challenge of developing applications that are successful. Page i Abstract Abstract The changing manufacturing environment is putting pressure on shop floor operators. To help them cope with the pressures and support them in their tasks an industrial hypermedia application, a computerised information system (IS), has been proposed. However, resistance to IS by target users is a widespread problem. Therefore, companies need guidance on how to augment user acceptance, hence success, of these applications. A literature review on industrial hypermedia applications revealed that five research issues needed to be investigated. Among those issues were the lack of recommendations to hypermedia application developers and managers of manufacturing companies intending to invest in industrial hypermedia applications. This research makes a major contribution by providing a set of recommendations that when adopted may produce successful applications benefiting both the operators and the manufacturing company. This research started by reviewing management of information systems (MIS), human computer interaction (HeI) and hypermedia disciplines to deduce a set of hypothesised factors or constructs that might influence success, measured through intention to use and subjective use. The factors, individual, organisational, task and system, were employed to develop two predictive and explanatory theoretical models, a pre-implementation and a post-implementation model. Empirical data for the constructs in the models were collected in the work place and statistically analysed. Based on the analysis, the ecologically valid findings suggest that shop floor operators can use industrial hypermedia applications and are rational when deciding whether or not to use the applications. The factor having a significant positive influence on user acceptance was an attribute of the application, namely perceived usefulness. The latter is influenced by other factors that can be controlled by developers and facilitated or mitigated by managers. With the proposed recommendations developers and managers may make informed decisions and meet the challenge of developing applications that are successful.